2012
DOI: 10.1590/s1679-62252012000100020
|View full text |Cite
|
Sign up to set email alerts
|

From forests to cattail: how does the riparian zone influence stream fish?

Abstract: The aim of this study was to verify whether taxonomic and functional composition of stream fishes vary under three different preservation conditions of riparian zone: preserved (PRE), intermediate condition (INT), and degraded (DEG). Five stream stretches representing each condition were selected. Samples were taken from each stream in three occasions during the dry seasons from 2004 to 2007. Electro fishing (PRE and INT), sieves, dip nets, and hand seines (DEG) were used according to the characteristics of ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
0
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(110 citation statements)
references
References 53 publications
5
88
0
13
Order By: Relevance
“…Based on the literature (Oyakawa et al, 2006;Casatti et al, 2012) species were categorized into trophic group, position in the water column and preference for rapid meso-habitats (Table 2). Seventeen metrics were considered to define the list of candidate metrics of the IBI (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the literature (Oyakawa et al, 2006;Casatti et al, 2012) species were categorized into trophic group, position in the water column and preference for rapid meso-habitats (Table 2). Seventeen metrics were considered to define the list of candidate metrics of the IBI (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…and KARR, JR. 1983 an increase in the amount of algae, macrophytes and debris. The presence of material of plant origin and a large variety of invertebrates, especially insects, are evidence for the omnivorous diet of Astyanax vermilion, that has a tendency towards insectivory, a condition that has been widely reported for species of the genus (Casatti et al, 2012;Castro and Casatti, 1997;Ferreira, 2007;Luiz et al, 1998).…”
Section: Resultsmentioning
confidence: 93%
“…This includes streams located in the Atlantic Forest (Menezes et al, 2007). These human actions generate great environmental impacts for stream structure (Lorion and Kennedy, 2009) and ichthyofauna (Casatti et al, 2012), making it difficult to maintain the integrity of these ecosystems Casatti et al, 2006). These alterations are particularly critical because, in headwater streams, the availability of resources, especially food, depends mostly on the surrounding environment, which is constantly providing organic and inorganic matter (Benstead et al, 2003;Pusey and Arthington, 2003;Allan, 1995;Lorion and Kennedy, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies (Allan, 2004;Casatti et al, 2006;Casatti et al, 2012) have showed the importance of riparian vegetation to the physical structure of streams, which can favor the maintenance of environmental stability and provide nutrients used through the trophic chain. Also, Rezende and Mazzoni (2005) have showed that in streams with riparian vegetation the input of allochthonous matter can change seasonally, with a higher input of animal-and vegetal matter during the wet season.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies (Bojsen and Barriga, 2002;Casatti, et al, 2012;Teresa and Casatti, 2012) have also showed the effects of riparian vegetation suppression on fish assemblage; i.e., it leads to their simplification, with a high dominance of tolerant species and loss of ecosystem services. Moreover, Casatti et al (2015) have found that although environments without riparian vegetation may have higher richness and diversity of fish, they also have a high functional redundancy, mostly related to feeding.…”
Section: Introductionmentioning
confidence: 99%